Foot planting techniques when sprinting at curves - Nemtsev, O.; Chechin, A. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The paper presents the research on foot and shin positioning at the moment of contacting the ground when sprinting at a curve. The results attained allow for expanding the knowledge of foot performance when running. The study revealed that experienced sprinters, when sprinting at curves at maximum speed, have their right and left foot toes turned outwards, the right foot being turned more due to the need to resist centrifugal force.